Natural product as chemoprevention from Maqasid Shariah perspective: a narrative review - Azalan, Maryam Syahidah; Abdul Ghani, Radiah (IIUM Press, 2023)
Chemoprevention strategies, which aim to prevent or reduce the risk of cancer using natural products, align with the Maqasid Shariah by promoting the preservation of life and the protection of health, which are fundamental objectives of Islamic law. This review aimed to understand the role of natural products (plants source) as chemoprevention from Maqasid Shariah viewpoint. The study of natural products as chemoprevention and their conceptualization are in parallel with the Al-Qur’an and As-Sunnah were found through a thorough search of the literature. Chemoprevention is a type of intervention that, in accordance with the first principle of Maqasid Shariah which emphasis on the preservation of life (hifz al-nafs). Several types of natural products from plant resources mentioned in Al-Qur'an and Al-Hadith for instance, dates, figs, olive, fennel, acacia, cucumber, pomegranate, ginger, onion, and black cumin possessed medicinal properties for disease treatments and anti-cancer effects. While different cancer types respond differently to natural products as anticancer agents, this review has identified categories of plants with chemopreventive efficacy in parallel with the concept of Maqasid Shariah that can serve as a guide for additional in-depth research in the biomedical sciences field.